Effects of aluminum sulfate on delta-aminolevulinate dehydratase from kidney, brain, and liver of adult mice - Schetinger,M.R.C. (1999)
The purpose of the present study was to investigate the in vitro and in vivo effects of aluminum sulfate on delta-aminolevulinic acid dehydratase (ALA-D) activity from the brain, liver and kidney of adult mice (Swiss albine). In vitro experiments showed that the aluminum sulfate concentration needed to inhibit the enzyme activity was 1.0-5.0 mM (N = 3) in brain, 4.0-5.0 mM (N = 3) in liver and 0.0-5.0 mM (N = 3) in kidney. The in vivo experiments were performed on three groups for one month: 1) control animals (N = 8); 2) animals treated with 1 g% (34 mM) sodium citrate (N = 8) and 3) animals treated with 1 g% (34 mM) sodium citrate plus 3.3 g% (49.5 mM) aluminum sulfate (N = 8). Exposure to aluminum sulfate in drinking water inhibited ALA-D activity in kidney (23.3 ± 3.7%, mean ± SEM, P<0.05 compared to control), but enhanced it in liver (31.2 ± 15.0%, mean ± SEM, P<0.05). The concentrations of aluminum in the brain, liver and kidney of adult mice were determined by graphite furnace atomic absorption spectrometry. The aluminum concentrations increased significantly in the liver (527 ± 3.9%, mean ± SEM, P<0.05) and kidney (283 ± 1.7%, mean ± SEM, P<0.05) but did not change in the brain of aluminum-exposed mice. One of the most important and striking observations was the increase in hepatic aluminum concentration in the mice treated only with 1 g% sodium citrate (34 mM) (217 ± 1.5%, mean ± SEM, P<0.05 compared to control). These results show that aluminum interferes with delta-aminolevulinate dehydratase activity in vitro and in vivo. The accumulation of this element was in the order: liver > kidney > brain. Furthermore, aluminum had only inhibitory properties in vitro, while in vivo it inhibited or stimulated the enzyme depending on the organ studied.